A fault estimation and fault-tolerant control based sliding mode observer for LPV descriptor systems with time delay - Hamdi, Habib; Rodrigues, Mickael; Rabaoui, Bouali; Benhadj Braiek, Naceur (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers the problem of fault-tolerant control (FTC) and fault reconstruction of actuator faults for linear parameter varying (LPV) descriptor systems with time delay. A polytopic sliding mode observer (PSMO) is synthesized to achieve simultaneous reconstruction of LPV polytopic descriptor system states and actuator faults. Exploiting the reconstructed actuator faults and state estimates, a fault-tolerant controller is designed to compensate the impact of actuator faults on system performance by stabilizing the closed-loop LPV delayed descriptor system.
Keywords: fault estimation; fault-tolerant control; LPV descriptor systems; sliding mode observers; time delay; LMIs